Effect of sowing date and weather parameters on turcicum leaf blight severity and yield in maize* - SRIKANT KULKARNI; YASHODA HEGDE, S.1. HARLAPUR, M.S. KULKARNI*, (Indian Phytopathology, 2007)
Field experiments were undertaken to determine the effect of sowing date and weather parameters on the severity of turcicum leaf blight of maize and their impact on maize yield. Disease severity gradually increased in the sowings till 16 September and later decreased. Maximum disease severity (75.37%) was recorded on the crop sown on 16 September that resulted in significantly lower yield (10.25 q/ha). Crop sown during I fortnight of April recorded minimum disease severity (26.75%) and significantly higher yield (25.88q/ha) was obtained with crop sown on 16 April. Relative humidity (> 70%), temperature (25-30Â°C)and rainfall (47-104mm) influenced maximum blight development. Relative humidity was the most important factor favouring disease development which showed significant and positive correlation with disease incidence while minimum and maximum temperatures had significant and negative correlations.